Frailty index and risk of delirium in hospitalized patients: a two-sample Mendelian randomization study - Chen, Yu; Feng, Fang; Li, Qun; Guo, Hong; Zhang, Lu; Liu, Jian (Frontiers in Medicine, 2024)
Objective: Observational studies suggest that the frailty index (FI) is closely related to delirium, but the relationship between them is still uncertain due to the influence of various confounding factors. Therefore, two-sample Mendelian randomization (MR) was used to explore the causal relationship between the FI and delirium risk. Methods: This study obtained pooled statistics for the FI and delirium from two of the most extensive genome-wide association studies. To make the results more robust and reliable, supplementary analyses were performed using several robust analytical methods (inverse-variance weighting, MR-Egger regression, and weighted median). In addition, this study used the MR-Egger intercept test, Cochran's Q test, funnel plots and the leave-one-out method to evaluate the pleiotropy and heterogeneity among the abovementioned genetic variation instrumental variables. Results: Frailty might increase the relative risk of delirium, as shown by IVW (OR = 1.849, 95% CI 0.027~2.067, P = 0.044), weighted median (OR = 1.726, 95% CI -0.178~2.664, P = 0.083), MR-Egger regression (OR = 1.768, 95% CI -3.08~6.171, P = 0.525) and leave-one-out sensitivity analysis (P = 0.058). Although the WME method and MR-Egger regression analysis showed no statistically significant causal relationship between the FI and the risk of delirium, the direction of the causal effect was consistent with the IVW method. Conclusion: There is a notable correlation between a higher FI and an elevated risk of delirium. This indicates that healthcare providers should take proactive measures to prevent delirium in hospitalized patients with a higher FI.